Climatic and elevational drivers of Selaginella species richness in Java, Indonesia - AHMAD DWI SETYAWAN; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO; SUNARTO SUNARTO; MUHAMMAD NUR SULTON (Nusantara Bioscience, 2026)
Abstract. Setyawan AD, Sutarno, Sugiyarto, Sunarto, Sulton MN. 2026. Climatic and elevational drivers of Selaginella species richness in Java, Indonesia. Nusantara Bioscience 18 (1): n180106. https://doi.org/10.13057/nusbiosci/n180106. Understanding environmental factors that shape species richness patterns, yet the determinants of Selaginella diversity in Java, Indonesia, remain poorly understood. Selaginella, an ancient lycophyte genus widely distributed in tropical regions, is highly sensitive to environmental conditions, particularly moisture availability and temperature. This study examined the relationships between Selaginella species richness and elevational and climatic gradients across Java, Indonesia. A total of 1,962 occurrence records representing 21 identified species and one unidentified taxon were compiled from field surveys, herbarium collections, and verified biodiversity databases. Species richness was estimated using a 0.25° × 0.25° grid system and spatially visualized through Inverse Distance Weighting (IDW) interpolation. The influence of elevation, Annual Mean Temperature, Annual Mean Precipitation, Annual Mean Solar Radiation, and Annual Mean Moisture Index on species richness was evaluated using polynomial regression, Pearson correlation analysis, and Principal Component Analysis (PCA). Species richness showed pronounced spatial heterogeneity, with hotspots concentrated in the humid montane regions of West Java. Richness exhibited nonlinear relationships with all environmental variables and peaked at intermediate elevations. Annual Mean Moisture Index (R² = 0.616) and Annual Mean Precipitation (R² = 0.527) were the variables most strongly associated with species richness, whereas Annual Mean Temperature and solar radiation showed negative relationships. Correlation and PCA results further indicated that moisture availability is closely linked to richness patterns, while elevation influences richness indirectly through its effects on local climatic conditions. These findings demonstrate that humid submontane and montane environments are critical for maintaining Selaginella diversity in Java and highlight the importance of conserving climatically suitable habitats under future environmental change.